Sustainable livestock production in semi-arid watersheds - Puskur, Ranjitha; Bouma, Jetske; Scott, Christopher A. (2004)
Watershed development programmes while exhibiting significant impacts in terms of Increased crop production and productivity, appear to have accentuated the inter- household inequities, by ignoring or sometimes negatively affecting landless and livestock, especially small-ruminant, owning households. Enhancing the production potential of a watershed for sustainable livestock production, would contribute to livelihood- and equity-enhancing impacts of the programmes. Appropriate policy and investment decisions are crucial to making this plausible.